Perspektif Mahasiswa Terhadap Strategi Pembelajaran Ilmu Ma’ani dalam Program International Student Mobility: Studi Kasus di Universitas Sultan Zainal Abidin / Student Perspectives on Learning Strategies for Ma'ani Studies in the International Student Mobility Program: A Case Study at Sultan Zainal Abidin University - Nadhilah Amalia Tauhidah; Farikh Marzuki Ammar; Mohammed Abdulaziz Eltigani (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
The International Student Mobility (ISM) program provides opportunities for students to contribute to cross-cultural learning experiences, including language proficiency, such as Ilmu Ma'ani. This study aims to examine the perspectives of students at Muhammadiyah University Sidoarjo (UMSIDA) regarding the Ilmu Ma'ani learning strategies applied by Sultan Zainal Abidin University (UniSZA) in the context of the ISM program. This study uses a qualitative case study approach involving 8 Arabic Language Education students from UMSIDA who participated in the ISM program. Data were obtained through participatory observation, interviews, and documentation, then analyzed using Miles and Huberman's theory, namely data reduction, data presentation, and data verification. The results of this study indicate that the learning strategies are dominated by a teacher-centered learning approach using lectures, trilingual application (Arabic-English-Malay), and hybrid-learning integration with the KeLIP, Webex, and Google Meet platforms. This study concludes that constructivism theory and cross-cultural learning theory (pedagogical and cross-cultural adaptation) have significant implications for the confidence and participation of international students during the learning process, reflecting educational efforts that are responsive and adaptive to the diversity of international students' backgrounds. This research is expected to serve as a reference for academic institutions in designing responsive and adaptive intercultural learning strategies in international mobility programs.Program International Student Mobility (ISM) memberikan peluang bagi mahasiswa untuk berkontribusi dalam pengalaman belajar lintas budaya, termasuk dalam penguasaan kebahasaan, seperti Ilmu Ma’ani. Penelitian ini bertujuan untuk mengkaji perspektif mahasiswa Universitas Muhammadiyah Sidoarjo (UMSIDA) terkait strategi pembelajaran Ilmu Ma’ani yang diterapkan Universitas Sultan Zainal Abidin (UniSZA) dalam konteks program ISM. Penelitian ini menggunakan pendekatan studi kasus kualitatif dengan melibatkan 8 mahasiswa Pendidikan Bahasa Arab UMSIDA yang mengikuti program ISM. Data diperoleh melalui observasi partisipatif, wawancara dan dokumentasi, kemudian dianalisis menggunakan teori Miles dan Huberman yaitu reduksi data, penyajian data, verifikasi data. Hasil penelitian ini menunjukkan bahwa strategi pembelajaran didominasi oleh pendekatan teacher-centered learning dengan metode ceramah, penerapan trilingual (Arab-Inggris-Melayu), serta integrasi hybrid-learning dengan platform KeLIP, Webex, dan Google Meet. Penelitian ini menyimpulkan bahwa teori konstruktivisme, dan teori cross-cultur learning berimplikasi secara signifikan terhadap kepercayaan diri, dan partisipasi mahasiswa internasional selama proses pembelajaran, sehingga mencerminkan upaya pendidikan yang responsif dan adaptif terhadap keragaman latar belakang mahasiswa internasional. Penelitian ini diharapkan dapat menjadi rujukan bagi lembaga pendidikan dalam merancang strategi pembelajaran antarkultural yang responsif dan adaptif dalam program mobilitas internasional.